Health education for early detection of breast cancer in blind women - Inacia Sátiro Xavier de França; Francisco Stélio de Sousa; Arthur Felipe Rodrigues Silva; Jamilly da Silva Aragão; Cibely Freire de Oliveira; Rosilene Santos Baptista (Universidade Federal do Ceará, 2015)
Objective: to assess the knowledge of blind women about the risk factors for breast cancer and whether they look for early detection of this cancer. Methods: a quasi-experimental study with 72 blind women distributed in focus groups. Data were collected through interviews. Results: few participants had knowledge about one or more risk factors for breast cancer, but most practiced early detection. Health education was developed using breast kits and demonstration of breast self-examination. It was obtained qualitative improvement of knowledge of the participants about breast cancer, its risk factors and early detection practices. In addition, participants demonstrated breast self-examination confidently. Conclusion: we need to develop in a harder manner educational activities to clarify about breast cancer risk factors and the importance of periodically carrying out breast self-examination, clinical examination and mammography.